Large genomic introgression blocks of Phaseolus parvifolius Freytag bean into the common bean enhance the crossability between tepary and common beans. (13th December 2022) - Barrera, Santos; Berny Mier y Teran, Jorge C.; Lobaton, Juan David; Escobar, Roosevelt; Gepts, Paul; Beebe, Steve; Urrea, Carlos A.
Abstract: The production of the common bean ( Phaseolus vulgaris L.), one of the most important sources of protein and minerals and one of the most consumed grain legumes globally, is highly affected by heat and drought constraints. In contrast, the tepary bean ( Phaseolus acutifolius A. Gray), a common bean‐related species, is adapted to hot and dry climates. Hybridization to introduce complex traits from the tepary bean into the common bean has been challenging, as embryo rescue is required. In this study, we report three novel interspecific lines that were obtained by crossing lines from prior common bean × tepary bean hybridization with Phaseolus parvifolius Freytag in order to increase the male gametic diversity to facilitate interspecific crosses. These interspecific lines enhanced the crossability of the common bean and tepary bean species while avoiding the embryo rescue process. Crossing these three interspecific lines with tepary beans resulted in 12‐fold more hybrid plants than crossing traditional common beans with tepary beans. Whole‐genome sequencing analysis of these three interspecific lines shows large introgressions of genomic regions corresponding to P. parvifolius on chromosomes that presumably contribute to reproductive barriers between both species. The development of these lines opens up the possibility of increasing the introgression of desirable tepary bean traits into the common bean to address constraints driven by climate change.